Stopping circulatory vaccine-derived poliovirus in Kaduna state by scaling up special interventions in local government areas along rivers of interest- kamacha basin experience, 2013-2015 - Audu I. Musa; Faisal Shuaib; Fiona Braka; Pascal Mkanda; Richard Banda; Charles Korir; Sisay G. Tegegne; Suleiman Abdullahi; Gregory C. Umeh; Terna I. Nomhwange; Hadiza Aliyu Iyal; Sambo Ishaku; et al. (BMC, 2018)
Abstract Background The Kamacha river is one of the five polio environmental surveillance sites in Kaduna State where 13 circulating vaccine-derived polioviruses (cVDPDs) were isolated between 2014 and 2015. Kamacha river accounted for 5 of all reported cVDPVs in Kaduna State between 2014 and 2015. Poor quality Supplemental Immunization Activities (SIAs) and low population immunity have been reported in the 10 LGAs with tributaries that flow into the river. We described the processes of implementing the various health interventions in these targeted LGAs along the Kamacha River and assessed the effectiveness of the interventions in stopping cVDPV in Kaduna, state, Nigeria. Methods Special interventions that had been proven to be functional and effective in reaching unreached children with potent vaccines in the state were scaled up in these targeted 10 LGAs along the Kamacha River. These interventions included revision of house based microplans, scaling up of transit vaccination, scaling up of youth engagement, intensified supportive supervision, scaling up of Directly Observed Polio Vaccination (DOPV) and in-between rounds vaccination activities. We analyzed immunization plus days (IPDs) administrative tally sheet and monitoring data from 10 rounds before and 10 rounds after the special interventions. Results The number of children immunized increased from 1,862,958 in December 2014 before the intervention to 1,922,940 in March 2016 after the intervention. Lot Quality Assurance Sampling (LQAS) results showed an increase in the proportion of LGAs accepted at coverage > 90% after the interventions, from 67% before intervention to 84% after intervention. The proportion of non-polio AFP children with > 4 doses of oral polio vaccine increased from 2 to 8% before to 93-98% after the interventions.. No new environmental cVDPV has been isolated since the introduction of the interventions in April 2015 until July 2016. Conclusion Scaling up known working interventions in the 10 LGAs with tributaries that drain to Kamacha River environmental sample site may have contributed to improved immunity and interruption of cVDPV in Kaduna state. These interventions should be replicated in LGAs and states with persistent poliovirus isolation.